2006
DOI: 10.1111/j.1365-2214.2006.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in children with Developmental Coordination Disorder

Abstract: The study has confirmed that children with DCD show varying profiles over a period of time and that the profiles have distinct characteristics related to events in the child's life. This approach to examining stability and change in the progressions of children's difficulties is in keeping with an ecological approach to explaining development with its multilayered influences creating changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
(27 reference statements)
0
17
0
2
Order By: Relevance
“…Learning disorders : Maughan & Hagell, 1996; Shaywitz et al 1999; Mattison et al 2002. Motor Disorder : Cantell et al 1994, 2003; Sugden & Chambers, 2007. PDDs : Howlin et al 2000, 2004; Mawhood et al 2000; Cederlund et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Learning disorders : Maughan & Hagell, 1996; Shaywitz et al 1999; Mattison et al 2002. Motor Disorder : Cantell et al 1994, 2003; Sugden & Chambers, 2007. PDDs : Howlin et al 2000, 2004; Mawhood et al 2000; Cederlund et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess motor impairment, the MABC (Henderson & Sugden, 1992) was selected as it is the most frequently used test to apply diagnostic criterion "A" (Geuze, Jongmans, Schoemaker, & Smits-Engelsman, 2001) that the child's motor coordination is "substantially below that expected" (American Psychiatric Association, 2000, p. 58). While it has been acknowledged that there are issues with repeating the MABC on occasions so close to each other, Sugden and Chambers's (2006) work suggested that a learning effect did not occur. It has been acknowledged that the MABC was designed as a screening tool rather than as an outcome measure but in the absence of a more suitable tool it was decided to use MABC and explore its utility as an outcome measure.…”
Section: Methodsmentioning
confidence: 91%
“…Our study has clinical implications. Physiotherapy or occupational therapy has been proven effective for treating motor problems, especially the task‐oriented and the cognitive‐based approaches like neuro motor task training (NMTt) and cognitive orientation to daily occupational performance (CO‐OP) (Niemeijer, Smits‐Engelsman, & Schoemaker, 2007; Sangster et al, 2005; Sugden & Chambers, 2007). These modern intervention methods are child‐focused and help children to acquire important skills for daily activities, which can increase their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have conclusively shown that physiotherapy of motor problems, especially child–centred, task‐oriented approaches, can ameliorate motor disability and thus quality of life (Sangster et al, 2005; Schoemaker et al, 2003; Sugden & Chambers, 2007; Watemberg et al, 2007; Wilson, 2005). Interventions can be delivered by physical therapists (which is usual in The Netherlands), or occupational therapists.…”
Section: Introductionmentioning
confidence: 99%